Hypomelanosis of Ito: report of two cases - Mohammad Abid Keen (Our Dermatology Online, 2015)
Hypomelanosis of Ito is a neurocutaneous disorder characterized by hypopigmented whorls, streaks and patches distributed along the lines of Blaschko, often associated with neurological and musculoskeletal abnormalities. We herein report two patients belonging to ethnic Kashmiri origin with this disorder